2013
DOI: 10.1128/iai.01459-12
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Response to Trypanosoma cruzi Infection Induces Secretion of Defensin α-1, Which Damages the Flagellum, Neutralizes Trypanosome Motility, and Inhibits Infection

Abstract: Human defensins play a fundamental role in the initiation of innate immune responses to some microbial pathogens. Here we show that colonic epithelial model HCT116 cells respond to Trypanosoma cruzi infection by secreting defensin ␣-1, which reduces infection. We also report the early effects of defensin ␣-1 on invasive trypomastigotes that involve damage of the flagellar structure to inhibit parasite motility and reduce cellular infection. Short exposure of defensin ␣-1 to trypomastigotes shows that defensin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 47 publications
(62 reference statements)
1
25
0
Order By: Relevance
“…Likewise the reduction of NK, F4/80 and Gr-1 cells observed at 24 h post-infection compared to their initial values might account for their marginalization in secondary lymphoid organs or tissues after exercising intense cytotoxic and phagocytic activity. Johnson et al (2013) showed the production of defensins with similar results. This phenomenon was observed previously in our model, in agreement with Arocena et al (2014), in which defensins secreted by Gr-1 cells along with other mediators might be responsible for the parasites' lysis and immobilization.…”
Section: Discussionsupporting
confidence: 86%
“…Likewise the reduction of NK, F4/80 and Gr-1 cells observed at 24 h post-infection compared to their initial values might account for their marginalization in secondary lymphoid organs or tissues after exercising intense cytotoxic and phagocytic activity. Johnson et al (2013) showed the production of defensins with similar results. This phenomenon was observed previously in our model, in agreement with Arocena et al (2014), in which defensins secreted by Gr-1 cells along with other mediators might be responsible for the parasites' lysis and immobilization.…”
Section: Discussionsupporting
confidence: 86%
“…In this regard, it is of interest that increasing the hydrophobicity of a bovine ␤-defensin 123-derived peptide had increased efficacy against MRSA with a 50% lethal dose of 3.91 g/ml in vitro (86). Human ␣-defensins are also effective against trypansomes (72,85), and therefore bovine ␤-defensins could provide novel trypanocidal treatments or breeding targets for one of the most important zoonotic pathogens in the developing world. Murine ␤-defensin-3 has also shown to have potent antiviral effects against influenza virus, both in vitro and in vivo (69).…”
Section: Alternatives To Antibioticsmentioning
confidence: 99%
“…Similarly, invasion to non-phagocytic cells exposed to cytochalasin D, indicate that trypomastigotes can penetrate actively into the cells (Ferreira et al, 2006). Additionally, exposure of trypomastigotes to defensin α-1, resulted in a damaged flagellum without affecting their viability; as a consequence parasite motility was altered and parasite infectivity reduced (Johnson et al, 2013). Whether the mechanism for a decrease in parasite infectivity was a result of energetic depletion was not assessed in this study.…”
Section: Discussionmentioning
confidence: 70%